Skin cancer knowledge and prevention practices: Turkish Bus Drivers - Nukhet Kirag; Serap Gokce Eskin (Journal of the Pakistan Medical Association, 2020)
Objective: To determine skin cancer knowledge levels and prevention practices among bus drivers. Methods: The cross sectional study was conducted in Ayd?n province, western Turkey, from April to June 2018, and comprised bus drivers who came to the primary health centre. Data was collected using a predesigned questionnaire based on sociodemographic characteristics and the Skin Cancer and Sun Knowledge Scale. Data was analysed using SPSS 16. Results: There were 125 male bus drivers with a mean age of 42.0±9.1 years. There was a significant relationship between history of skin cancer in the family and the presence of freckles (p<0.05). Those who were exposed to the sun for one or two hours a day scored higher on the knowledge scale than those with a sun exposure of >2 hours a day (p<0.05). Conclusion: The bus drivers did not have enough knowledge about the critical significance of skin cancer. Key Words: Sun protection, Drivers, Skin, Cancer, Turkey. Continuous...